2014
DOI: 10.1242/jcs.138388
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cavernous malformation proteins at a glance

Abstract: Loss-of-function mutations in genes encoding KRIT1 (also known as CCM1), CCM2 (also known as OSM and malcavernin) or PDCD10 (also known as CCM3) cause cerebral cavernous malformations (CCMs). These abnormalities are characterized by dilated leaky blood vessels, especially in the neurovasculature, that result in increased risk of stroke, focal neurological defects and seizures. The three CCM proteins can exist in a trimeric complex, and each of these essential multi-domain adaptor proteins also interacts with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 88 publications
0
85
0
Order By: Relevance
“…Normal endothelial basement membranes are composed mainly of collagen IV, laminin, and other glycoproteins and proteoglycans. Both flow-dependent remodeling and sprouting angiogenesis require proteolysis of this ECM and assembly of a fibronectin matrix (63)(64)(65) (108,110). Patients acquire sporadic lesions with age, presumably due to additional mutations or other local stresses, though these additional events are not well characterized.…”
Section: Plaque Progression and Remodelingmentioning
confidence: 99%
“…Normal endothelial basement membranes are composed mainly of collagen IV, laminin, and other glycoproteins and proteoglycans. Both flow-dependent remodeling and sprouting angiogenesis require proteolysis of this ECM and assembly of a fibronectin matrix (63)(64)(65) (108,110). Patients acquire sporadic lesions with age, presumably due to additional mutations or other local stresses, though these additional events are not well characterized.…”
Section: Plaque Progression and Remodelingmentioning
confidence: 99%
“…However, KRIT1 is a multidomain protein that, in addition to having several other binding partners, contains two putative NLS and one predicted nuclear export signal (NES) (Fig. 7A) (17,28,30,43,44). To determine the localization of full-length KRIT1 (KRIT1 FL ) and the role of the predicted NLS and NES in the absence of co-expressed ICAP1, GFP-tagged KRIT1 was overexpressed in CHO cells (which do not express either endogenous ICAP1 or KRIT1 (45)).…”
Section: Binding To Icap1 Drives Nuclear Localization Of the Nterminamentioning
confidence: 99%
“…CCMs have been reported in up to 0.5% of the population (16) and are strongly associated with hemorrhagic stroke, seizure, epilepsy, and other focal neurological outcomes. CCMs are also caused by loss of function mutations in CCM2 or CCM3 genes (17), and the CCM2 protein can form the hub of a multiprotein KRIT1-CCM2-CCM3 complex: the CCM complex (12,18,19). Loss of KRIT1, CCM2, or CCM3 proteins is therefore directly associated with focal neurological defects, stroke, and vascular abnormalities.…”
mentioning
confidence: 99%
“…Mutations of the CCM3 gene have been linked to cerebral cavernous malformations -vascular abnormalities characterised by dilated leaky cerebral lesions that can lead to brain haemorrhage (Draheim et al, 2014). The exact mechanism by which cerebral cavernous malformations arise is still subject to debate, with deregulation of several signalling pathways such as RHO (Richardson et al, 2013;Stockton et al, 2010;Borikova et al, 2010;Whitehead et al, 2009), TGFβ (Maddaluno et al, 2013), β-catenin (Bravi et al, 2015) and MEKK3-KLF2 or MEKK3-KLF4 (Cuttano et al, 2016;Zhou et al, 2016;Renz et al, 2015) having been demonstrated to be involved in development and progression of the disease.…”
Section: E-2mentioning
confidence: 99%